Heavily Indebted Poor Countries Initiative : Status of Implementation. (Policy Papers; Policy Paper ;, 2005)
This report reviews progress and issues in implementing the enhanced HIPC Initiative. In addition to updating information on the delivery of HIPC debt relief and its estimated costs, it discusses two particular issues: the decline in the participation of commercial and non-Paris Club bilateral creditors to the Initiative; and the preliminary list of countries that satisfy the indebtedness eligibility criterion under the extended HIPC sunset clause.